Strategi Pemasaran Pendidikan Islam - Sarohmad, Sarohmad (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
The marketing strategy is the most important part that must be owned by the institution in order to maintain its existence. The rapid competition in the world of education, which causes the pace of global development, continues to demand that educational institutions be more competitive. The method used in this research is qualitative with a case study type. Data and data sources were obtained from informants at the Batu Bilingual MA institution through interview, observation, and documentation techniques. The results of the study indicate that the marketing strategy implemented by MA Bilingual Batu can be identified by a number of strategies that are relevant to marketing strategies that are generally carried out in the business world. These strategies include product, price, place, promotion, people, physical evidence, and process. The marketing strategy development carried out by MA Bilingual Batu, namely, the first is the guerrilla strategy (face-to-face, guerrilla strategy, leadership strategy for the Madrasah Principal, uniqueness strategy, strategy for publicising achievements, and strategy for awarding scholarships),